Islamic Pedagogy Resilience: Exploring Strategies for Social Character Development Beyond the Pandemic - Arti Suci Muliyani; Sadam Fajar Shodiq; Abeer Mohammed Ali (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This empirical study examines the resilience tactics utilized in Islamic pedagogy to foster the growth of social character qualities in spite of the difficulties presented by the Covid-19 epidemic. The research is centered around SMA Negeri 7 Yogyakarta and seeks to uncover the creative methods employed by Islamic Education instructors in fostering students' social traits both during and after the pandemic. The study employed qualitative research methods such as observation, interviews, and recording. The participants included school administrators, student assistants, Grade 12 Islamic Education teachers, and two students from SMA Negeri 7 Yogyakarta. This study examines the diverse approaches utilized by Islamic Education instructors, specifically in response to the pandemic's influence on students' social growth. The findings suggest that Grade 12 Islamic Education teachers overcome these problems by employing resilient tactics, including the use of role models, offering mentorship, and fostering interactive and socially conscious learning settings. The report also emphasizes the prospects and difficulties faced by educators in this endeavor, such as cultivating connections with kids from various backgrounds, inculcating ethical and moral comprehension, and actively engaging parents in the journey of character development. This research enhances the overall comprehension of Islamic pedagogy resilience and its impact on the development of social character beyond the pandemic. It highlights the crucial role educators play in molding students' characters in the changing educational environment.